2017
DOI: 10.12678/1089-313x.21.3.109
|View full text |Cite
|
Sign up to set email alerts
|

Height of the Medial Longitudinal Arch During Classical Ballet Steps

Abstract: The purpose of this study was to evaluate the midfoot longitudinal arch height and correlate it with active hip external rotation (ER) in dancers during static postures and technical steps of classical ballet (i.e., first position, demi-plié, battement fondu à la seconde, pas jeté à la seconde, and grand jeté à la seconde). A 3D motion analysis system was used for kinematic analysis. The arch height was significantly reduced during the battement fondu à la seconde, pas jeté à la seconde, and grand jeté à la se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 27 publications
(45 reference statements)
1
19
0
Order By: Relevance
“…Regardless of foot position, lack of visual information reduced stability (especially for CoP parameters, anteroposterior and mediolateral GRF components) in both groups, as has been shown previously [4,17,21]. The ballet dancers showed greater dependence on visual information for postural control.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Regardless of foot position, lack of visual information reduced stability (especially for CoP parameters, anteroposterior and mediolateral GRF components) in both groups, as has been shown previously [4,17,21]. The ballet dancers showed greater dependence on visual information for postural control.…”
Section: Discussionsupporting
confidence: 69%
“…The analysis of dynamic strategies during the "grand plié" is an essential step in understanding and preventing injury. The "grand plié" is not challenging for ballet dancers, however it is an essential basic ballet movement that is practiced daily from the very first lessons [21]. As a result of training, dancers develop specific motor strategies to achieve this movement, which are more effective than those of non-dancers [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with kinematics evaluations of dancers with and without low back pain, that is, assessments of the articular movement of the lumbosacral spine and the hip joint, show that pain does not influence the joint mobility of the spine of dancers with low back pain [ 22 , 23 ]. Studies on ankle kinematics [ 20 ] observed that a significant decrease in the height of the medial longitudinal arch can induces decreases in the body stability during landing in jumping movements [ 46 ]. Thus, the foot support base is a main key point for integrating greater body stability and balance for dancers [ 7 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Schober clinical test was performed to assess the flexibility of the thoracic and lumbosacral spine on sagittal plane during anterior trunk flexion [ 46 ]; with previously demonstrated validity and reliability [ 35 , 36 ]. To perform this test, each individual was barefoot; and the region of the lumbosacral spine was free of clothing to enable the examining physiotherapist to delimit the anatomical points.…”
Section: Methodsmentioning
confidence: 99%